The Implementation of Special Box Learning Media in Developing Students’ Critical Thinking Skills in Pancasila Education at SDN Daramista II - Khairul Faizin; Indah Ramadhani; Yetti Hidayatillah; Muhammad Misbahudholam AR (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
The critical thinking ability of elementary school students is still relatively low, especially in Pancasila Education subjects which tend to be theoretical and do not actively involve students. The researcher conducted this study with the aim of finding out how the Special Box learning media can be applied to improve the critical thinking ability of grade VI students at SDN Daramista II. This study used a mixed method with a sequential exploratory approach, which combines qualitative data through observation, interview, and documentation techniques, as well as quantitative data obtained from questionnaires and critical thinking ability tests. Based on the results of the study, the use of the Special Box media designed with the Contextual Teaching and Learning and Discovery Learning approaches has been proven to be able to significantly increase student participation and encourage their cognitive involvement. Students showed enthusiasm, courage in answering challenges, and the ability to link Pancasila values ​​to real life. Quantitative findings support these results with the majority of students giving a